Academical training of Health Sciences professionals as a resource to integrate teaching, assistance and research - Norma Mur Villar; Miriam Iglesias León; María José Aguilar Cordero; Yaan Manuel Quintana Santiago; Manuel Eduardo Cortés Cortés (Medisur)
Academic training of Health Sciences professionals is an essential resource to integrate teaching, assistance and research and should be considered as an inherent attribute of professional practice. In present times this issue is still being questioned, because educational practice has not been fully transformed in the clinical setting. This work supports the potentials of academic training in Health Sciences to achieve this integration and is a call for professionals to create scientific basis of educational knowledge production in order to link health care practice to teaching and research. Bibliographic analysis showed that assistance centers should be academic centers for the development of Health Sciences. Academic training of professionals enables the integration we are looking for and establishes a mutual empowerment relationship, where each dimension is favoured in its interface.